Senso de posição articular em atletas femininas de handebol e voleibol - Teixeira, Lilian Pinto (2019)
The shoulder is a naturally unstable joint that is essentially dependent on muscles and neuromuscular control for stability. Physiological adaptations in the glenohumeral joint are expected in throwing athletes due to repetitive and atraumatic shoulder movement in sports, which may lead to proprioceptive deficits. Proprioception can be divided three submodalities: joint position sense, kinesthesia, and force sense. The active joint repositioning test is considered one of the most functional ways of assessing joint position sense. The aim of this study was to compare shoulder joint position sense in female handball and volleyball athletes. Ninety-two handball (n = 56) and volleyball (n = 36) individuals from the city of Santa Maria, aged 13 to 24 years and without symptoms in the shoulder and neck region were evaluated. The assessment of joint position sense was performed by active joint repositioning test using a digital inclinometer (Acummar - model ACU001). During the tests, the subjects remained blindfolded and used a headset to decrease visual and auditory feedback, respectively. The movements evaluated were shoulder scaption (target angles of 55º, 90º and 125 °) and external rotation (60º and 80 °). The constant error in the repositioning test was analyzed using two-way repeated measures ANOVA, considering sports, age and training time factors between subjects and target angle as intra-subject factor. The tests were performed at a significance level of 5% and all statistical analyzes used the SPSS Windows program (SSPS, Chigaco, IL, USA). There was interaction between sport and angle in the shoulder lift repositioning test, with handball athletes performing worse at 90 ° when compared to 55 ° and volleyball athletes with greater errors at 125 ° than 55 ° and 90 °. The largest repositioning errors occurred at the highest amplitudes for lift movement, with no differences for rotational motion. Younger athletes with shorter training time performed worse in their joint position sense. These results demonstrate differences in joint position sense in volleyball and handball athletes that can guide preventive strategies, especially in younger and inexperienced athletes.